2003
DOI: 10.1078/0944-5013-00173
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium graminearum and deoxynivalenol contamination in the durum wheat area of Argentina

Abstract: Fusarium graminearum head blight of wheat is a destructive disease of the world's wheat-growing areas. This work was performed to analyze the distribution and contamination of deoxynivalenol (DON) and its relationship with F. graminearum kernel invasion in Argentina durum wheat area during two consecutive harvests. A total of 147 samples (cultivars and lines) of durum wheat from 5 locations of the major cropping area (Southern Buenos Aires Province) were analyzed. Percentage of F. graminearum kernel infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 14 publications
5
33
0
4
Order By: Relevance
“…Most of the samples analyzed were above the maximum DON limit proposed by the EC (2007) and FAO (2004). The DON levels detected in the 2012/13 FHB epidemic year are similar to those detected in previous epidemic years in Argentina (Lori et al 2003). DON has been reported as the main Fusarium mycotoxin in wheat and by-products in South America; with Argentina, Brazil and Uruguay the countries with available information (Del Ponte et al 2012;Umpiérrez et al 2013).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Most of the samples analyzed were above the maximum DON limit proposed by the EC (2007) and FAO (2004). The DON levels detected in the 2012/13 FHB epidemic year are similar to those detected in previous epidemic years in Argentina (Lori et al 2003). DON has been reported as the main Fusarium mycotoxin in wheat and by-products in South America; with Argentina, Brazil and Uruguay the countries with available information (Del Ponte et al 2012;Umpiérrez et al 2013).…”
Section: Discussionsupporting
confidence: 58%
“…The 2012 FHB epidemic affecting Argentina was also reported in Uruguay (Umpiérrez et al 2013). In a previous study, Lori et al (2003) reported similar levels of F. graminearum infection (up to 52.3%) during a favorable year for FHB, although strains were isolated from durum wheat in Argentina.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The evaluation of the incidence of mycotoxigenic mold in food is important because of the strong correlation between mold presence and mycotoxin occurrence (González et al, 1998;Lori et al, 2003;Passone et al, 2010). The information resulting from these tests can indicate the hazard analysis critical control point inside the food producer chain (Food and Agriculture Drganization of the United Nations, 2001) and allows decision-making measures about the storage time of the analyzed product and the need for specific mycotoxin analysis.…”
Section: Introductionmentioning
confidence: 99%